Rapid Detection of Microbial Profile among Women with Vaginitis in Hilla City, Iraq - Hussein Oleiwi Muttaleb Al-Dahmoshi (Journal of Applied Pharmaceutical Science, 2017)
Bacterial vaginosis is a complex, polymicrobial infection ascribed to an overgrowth of strict or facultative anaerobic bacteria or unconventionally cultivate bacteria like Mycoplasma hominis, Ureaplasma urealyticum. It is the most common cause of vaginal discharge among women in reproductive age. The malodorous vaginal discharge resulted from production of amines like putrescine, cadaverine and trimethylamine due to bacterial deamination reactions. Forty vaginal swabs were collected from a marriage women with age (mean ± SD= 31.8±7.57) during the period from October 2014 to January 2015. All patients visit gynecology clinic in Al-Mahaweel hospital. All swabs immersed in physiological solution and then loaded to AF genital system plate. The results revealed that 22(55%) attributed to polymicrobial bacterial vaginosis, 1 (2.5%) for trichomoniasis and 2(5%) for candidiasis as a single agent vaginitis. Mix infection, double agent vaginitis were 13(32.5%). Low percent of multiple agent vaginosis were recorded 2 (5%) which include bacterial vaginosis, trichomoniasis and candidiasis at the same swab. Staphylococcus aureus compile 32(80%), Enterococcus faecalis 26(65%), Streptococcus agalactiae 12(30%), Mycoplasma hominis 10(25%), Ureaplasma urealyticum 7(17.5%), Gardnerella vaginalis 10(25%), Proteus spp./Providencia spp. 8(20%), E. coli 6(15%) while Neisseria gonorrhoeae and Psudomonas spp. not detected while 3(12.5%) for T. vaginalis and 15(37.5%) for Candida spp. Antibiotic susceptibility results for Mycoplasma hominis and Ureaplasma urealyticum show total sensitivity to clindamycin and pefloxacin while resisted to the other in different percentage (5%-15%). This study conclude that, bacterial vaginosis compile high percentage among women with vaginal discharge. It can be present alone or along with candidiasis while rare cases record a combined infection of bacterial vaginosis along with trichomoniasis and both candidiasis and trichomoniasis may be as secondary infection that enhanced after bacterial vaginosis. Also conclude excellent response to treatment with tetracycline and new fluoroquinolones such as pefloxacin.
Keywords: Bacterial vaginosis, Mycoplasma hominis, Ureaplasma urealyticum.